(untitled) (Journal of the College of Basic Education, 2024)
Germany came out of the Second World War surrendered and economically destroyed, infrastructure, factories, housing and transportation were destroyed, and Germany turned from a prosperous country with its economic potential to a weak country under the control of the victorious countries, All these difficult conditions and the continued collapse of the economic conditions in Germany is tantamount to strengthening the communist movements, which found in those conditions the appropriate climate for their call, and hence the United States of America established the European program to help Germany restore its economy, and this assistance was a major factor in Germany’s return to the economic superpower, as Germany began to build factories and operate The other factor behind the German Renaissance is the industrial revolution that took place in Germany in various fields, especially in Heavy Industries, and it was helped in this by relying on specialists in the management of Germany’s economic policy, including Ludwig Erhard, the first German minister of economy in the government of Konrad Adenauer.